Letter to Mrs. Daniel Tolmach; Camarillo State Hospital from F.H Garrett - F.H. Garrett:::::: (1960)
Letter to Mrs. Daniel Tolmach and the Camarillo State Hospital from F.H. Garrett (Superintendent and Medical Director) sent on May, 18, 2024. This short letter is a notice announcing that the Senate Committee hearing at the Camarillo State Hospital will be postponed until further notice. The possible dates that this hearing will be be scheduled on is June 16th of June 23rd.